Apocalypse then : The Evolution of the North Atlantic Economy and the Global Crisis - Bui, Trung (IMF Working Papers; Working Paper ;, 2011)
The financial crisis, originated from the collapse of US housing markets in 2008, reverberates around the world. Its destructive force was felt nowhere more keenly than Western Europe. Indeed, it continues to mire in financial volatility as the debt problem contagiously spreads around the periphery Euro area. Taking a wider historical view of the evolution over the recent decades of the North Atlantic economy, comprising North America and Western Europe, we argue that while trade links were in relative stasis, the increasing and uniquely-close Transatlantic financial relationship was a crucial conduit in transmitting US shocks into global ones.